Investigation of agency and mental wellbeing : the case of international students in the context of Finnish higher education - Roshanizand, Faraz (2020)
The Agency of higher education students has been extensively discussed in the context of learning (Baxter, 2019; Zeiser, Scholz, & Cirks, 2018). Meanwhile, the mental wellbeing of the international students and the constraints towards maintenance of it have been studied mostly in English-speaking countries (Alharbi, & Smith, 2018) . This thesis investigates and analyzes how agency is exercised by international students. Further, constraints and supporters of their mental wellbeing in the context of Finnish higher education are examined in a new context. Observations and experiences of the author together with the secondary link that was found in literature between agency and mental wellbeing were the main rationale to look at these concepts within the framework of this research. The data was gathered through seven qualitative semi-structured individual interviews from international students. The analysis of the data was done with the utilization of deductive content analysis. The findings showed various problems like, creation of a new social circle and cultural assimilation hinder the mental wellbeing of students; as opposed to factors like having a sense of belonging or well-functioning university support systems that scaffold mental wellbeing . Moreover, exercise of agency was manifested in activities like being proactive or self-reflective. I t was concluded that universities should take up an active role to promote their students’ agency in order to enable them and consider ways to sustain a balanced mental wellbeing for them. In conclusion, more attention, acknowledgement and consideration are required to handle mental wellbeing and agency of international students.